1995
DOI: 10.1093/ajcn/62.1.250s
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sugars and lipid metabolism in humans

Abstract: When large amounts of sugars are included in the diets of humans and other animals, alterations in concentrations of plasma lipid constituents may be observed; usually elevation of triacylglycerol concentrations and sometimes elevation of low-density-lipoprotein cholesterol and depression of high-density-lipoprotein cholesterol. These effects are not seen with amounts of sugars typical of those in the Western diet, although more information is needed on postprandial triacylglycerol concentrations, which may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 117 publications
3
80
1
Order By: Relevance
“…This switch can be calculated to account for an approximate reduction of 20 GI units when compared to the predicted GI of the food if sucrose has been used, and was therefore responsible for almost half of the 50-unit difference seen between the white bread and the functional food prototypes. Some studies (Frayn & Kingman, 1995;Bantle et al, 1992), but not all (Malerbi et al, 1996), have shown deleterious effects on serum triglycerides and LDL cholesterol levels when fructose intakes are 20% of energy. Generally, moderate intakes of fructose have been considered acceptable (American Diabetes Association, 1999;Wolever et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This switch can be calculated to account for an approximate reduction of 20 GI units when compared to the predicted GI of the food if sucrose has been used, and was therefore responsible for almost half of the 50-unit difference seen between the white bread and the functional food prototypes. Some studies (Frayn & Kingman, 1995;Bantle et al, 1992), but not all (Malerbi et al, 1996), have shown deleterious effects on serum triglycerides and LDL cholesterol levels when fructose intakes are 20% of energy. Generally, moderate intakes of fructose have been considered acceptable (American Diabetes Association, 1999;Wolever et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An additional strategy to increase palatability and at the same time lower the GI of the food is to substitute fructose for sucrose, as the GI for fructose is 29, while that for sucrose is 84 (Jenkins et al, 1981). Health agencies recognize the reduced glucose response to fructose (Diabetes and Nutrition Study Group of the European Association for the Study of Diabetes, 1995;American Diabetes Association, 1999;Wolever et al, 1999), but advise moderate intake since excessive intake (20% of calories) may raise serum triglyceride (Frayn & Kingman, 1995) and possibly low-density lipoprotein (LDL) cholesterol (Bantle et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…High plasma insulin concentrations are associated with insulin resistance and increased risk for coronary heart disease (DeFronzo & Ferrannini, 1991) and it is believed that fructose and sucrose may raise plasma triglycerides, at least in part, because they elicit high plasma insulin responses that stimulate hepatic lipogenesis (Frayn & Kingman, 1995). Several studies have compared the glycaemic effects of sugars with those of starchy foods (Foster-Powell & Brand Miller, 1995) but many of these did not include a measure of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on the effects of high-carbohydrate diets (b 55% of energy from CHO) on plasma lipids show a rise in fasting plasma triacylglycerol concentrations mainly re¯ecting an increase in VLDL-triacylglycerol concentration (Frayn & Kingman, 1995). The effects of a high-CHO, lowfat diet on plasma lipid concentration (increased fasting plasma triacylglycerol, and decreased HDL-cholesterol concentrations) appear to be mainly mediated by increased sucrose and fructose intake (Coulston et al, 1983;Hudgins et al, 1995).…”
Section: Recommended Fat Intake For Adultsmentioning
confidence: 99%
“…In these diets, carbohydrate replaces the energy from fat, creating the risk for inducing a rise in plasma triacylglycerol by an increased hepatic secretion of very-low-density-lipoprotein (VLDL) triacylglcyerols andaor a decrease in the catabolic rate of VLDL triacylglycerols (Blades & Garg, 1995). The question then arises as to whether a low-fat diet, which is necessarily relatively high in carbohydrate, may itself lead to adverse changes in blood lipids.Most studies on the effects of high-carbohydrate diets (b 55% of energy from CHO) on plasma lipids show a rise in fasting plasma triacylglycerol concentrations mainly re¯ecting an increase in VLDL-triacylglycerol concentration (Frayn & Kingman, 1995). The effects of a high-CHO, lowfat diet on plasma lipid concentration (increased fasting plasma triacylglycerol, and decreased HDL-cholesterol concentrations) appear to be mainly mediated by increased sucrose and fructose intake (Coulston et al, 1983;Hudgins et al, 1995).…”
mentioning
confidence: 99%